2023
DOI: 10.1039/d2ay00995a
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing extraction solvents for deoxynivalenol analysis in maize via infrared attenuated total reflection spectroscopy and chemometric methods

Abstract: Farmers, cereal suppliers and processors demand rapid techniques for the assessment of mould-associated contamination. Deoxynivalenol (DON) is among the most important Fusarium toxins and related to human and animal diseases...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…This could be attributed to the distinct chemical composition of maize and wheat and/or the nature of the fungal contamination: the type of fungal strains grown, which metabolites they produce, and how they degrade the food matrix. 31 The high classification accuracy of the models achieved in the present study is indeed consistent with the literature. Several other studies that applied IR-ATR spectroscopy for mycotoxins analysis in cereals or other matrices demonstrate Acc cv > 90%.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This could be attributed to the distinct chemical composition of maize and wheat and/or the nature of the fungal contamination: the type of fungal strains grown, which metabolites they produce, and how they degrade the food matrix. 31 The high classification accuracy of the models achieved in the present study is indeed consistent with the literature. Several other studies that applied IR-ATR spectroscopy for mycotoxins analysis in cereals or other matrices demonstrate Acc cv > 90%.…”
Section: Discussionsupporting
confidence: 92%
“…No evidence was found that this clustering influences the classification according to the DON levels. 31 From the obtained SPLS-DA results (Table 2), it is evident that all the models show a high classification accuracy of crossvalidation (Acc cv > 0.840). The prediction models exhibit high values of sensitivity and specificity, suggesting a balanced classification of both classes: low and high DON (Table 2).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations